2002
DOI: 10.1016/s0022-5347(05)65392-x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Serum Prostate Specific Antigen Levels Between 2 and 22 Ng./Ml. Correlate Poorly With Post-Radical Prostatectomy Cancer Morphology: Prostate Specific Antigen Cure Rates Appear Constant Between 2 and 9 Ng./Ml.

Abstract: Preoperative serum PSA has a clinically useless relationship with cancer volume and grade in radical prostatectomy specimens, and a limited relationship with PSA cure rates at preoperative serum PSA levels of 2 to 9 ng./ml. Trend summaries for prostate weight on broken line regression showed that below 9 ng./ml. BPH is a strong contender for the cause of PSA elevation, constituting the primary cause of the over diagnosis of prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
1
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(94 citation statements)
references
References 36 publications
7
81
1
4
Order By: Relevance
“…In populations regularly exposed to screening, levels of tPSA decrease significantly and eventually lose association with important disease characteristics. This is exemplified by recent reports from Stamey et al who found that tPSA did not predict treatment outcome after RP in men with tPSA from 2 to 9 ng/ml, 8 and a series of 1095 men with tPSA 10 ng/ml studied by Freedland et al who concluded that PSA was not an independent predictor of biochemical failure following RP in a multivariable model (p 5 0.09). 7 Hence, it is highly controversial whether tPSA remain as a significant predictor of treatment failure among men with a more narrow range of serum tPSA.…”
Section: Discussionmentioning
confidence: 82%
“…In populations regularly exposed to screening, levels of tPSA decrease significantly and eventually lose association with important disease characteristics. This is exemplified by recent reports from Stamey et al who found that tPSA did not predict treatment outcome after RP in men with tPSA from 2 to 9 ng/ml, 8 and a series of 1095 men with tPSA 10 ng/ml studied by Freedland et al who concluded that PSA was not an independent predictor of biochemical failure following RP in a multivariable model (p 5 0.09). 7 Hence, it is highly controversial whether tPSA remain as a significant predictor of treatment failure among men with a more narrow range of serum tPSA.…”
Section: Discussionmentioning
confidence: 82%
“…[5][6][7] Changes in the epidemiology of PCa have strongly limited the correlation between total PSA and the stage of PCa. [8][9][10] PSA can no longer be considered as a classical tumor marker whose levels are directly correlated with increasing stage of the disease. Moreover, the relationship with tumor grade remains unclear since it has been suggested that total PSA expression decreases with higher Gleason scores.…”
Section: Introductionmentioning
confidence: 99%
“…Screening for prostate speciWc antigen (PSA) in asymptomatic populations has increased the detection rate of prostate cancer as well as the number of surgical and radiotherapeutic treatments. Recently, the use of PSA as a diagnostic marker has come to be discussed (Stamey et al 2002). An elevated level of serum PSA not only detects aggressive malignancy but it is also associated with benign prostate hyperplasia (BPH) and with mildly aggressive, slowly progressing, neoplasia.…”
Section: Introductionmentioning
confidence: 99%